Pancreaticobiliary malignancy masquerading as tuberculosis: A caseof multifocal skeletal and hepatic metastases - Ray, Girin; Gupta, Chandra Paul; Basu, Satyaki (Indian Journal of Case Reports, 2026)
A 41-year-old female with remote treated pulmonary tuberculosis (TB) presented with 4 months of progressive back pain and dry cough. Magnetic resonance imaging of the dorso-lumbo-sacral spine revealed multifocal altered marrow signals in multiple vertebrae and both iliac bones, consistent with osseous metastases. Triphasic computed tomography of the abdomen demonstrated multiple peripherally enhancing hepatic nodules with inner cystic change (largest 35 × 31 mm), common bile duct widening to 6 mm with diffuse wall thickening, and bilateral pleural effusions with a left basal soft-tissue lesion. Pleural fluid analysis showed CA19-9 >1000 U/L, lactate dehydrogenase 856.2 U/L, adenosine deaminase 11.1 U/L, glucose 35 mg/dL, and total protein 4.1 g/dL, consistent with malignant exudative effusion. A prior history of TB and overlapping symptoms created diagnostic anchoring bias. The patient developed sepsis and succumbed before histopathological confirmation. This case underscores the critical importance of tumor marker profiling, multimodal imaging, and early oncologic referral in patients with multifocal skeletal and hepatic lesions, regardless of prior TB history